2012
DOI: 10.1038/oby.2011.399
|View full text |Cite
|
Sign up to set email alerts
|

Axl Deficiency Does Not Affect Adipogenesis or Adipose Tissue Development

Abstract: To evaluate a potential role of Axl, the high‐affinity receptor of growth arrest‐specific protein 6 (GAS6) in adiposity, murine embryonic fibroblasts (MEF) derived from mice with genetic deficiency of Axl (Axl−/−) or wild‐type littermates (Axl+/+) were differentiated into mature adipocytes. In addition, Axl−/− and Axl+/+ mice were kept on standard fat diet (SFD) or on high‐fat diet (HFD) for 15 weeks. Deficiency of Axl in MEF did not affect differentiation, as shown by a similar uptake of Oil Red O and express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 19 publications
(28 reference statements)
0
19
2
1
Order By: Relevance
“…Our findings indicated that AXL gene polymorphisms might not play a significant role in childhood obesity. Recently, Scroyen and colleagues [37] have published similar findings indicating that deficiency in a single Axl receptor did not significantly affect adipogenesis or adipose tissue development in mice. This is because an Axl deficiency can be partially compensated by other TAM family members (Tyro-3 and Mer) via Gas6 interaction.…”
Section: Discussionmentioning
confidence: 89%
“…Our findings indicated that AXL gene polymorphisms might not play a significant role in childhood obesity. Recently, Scroyen and colleagues [37] have published similar findings indicating that deficiency in a single Axl receptor did not significantly affect adipogenesis or adipose tissue development in mice. This is because an Axl deficiency can be partially compensated by other TAM family members (Tyro-3 and Mer) via Gas6 interaction.…”
Section: Discussionmentioning
confidence: 89%
“…As the mouse phenotypes were not due to behavioral changes in food intake or in activity levels, it led to the hypothesis that GAS6-Axl activation may directly impair glucose and lipid metabolism in peripheral organs. However, the global Axl-KO mice did not show any difference in body weight gain or subcutaneous and gonadal fat mass under either standard or high-fat diet (Scroyen et al, 2012). This could be due to compensatory effects by the other two TAM receptors that were upregulated in the Axl-KO mice (Scroyen et al, 2012).…”
Section: Tam Receptor Familymentioning
confidence: 85%
“…To monitor insulin signaling, analysis of Akt and Phospho (P) Akt in extracts of SC or GON adipose tissues was performed using the primary antibodies Akt or P-Akt (9272 or 9271, Cell Signaling Technology, Danvers, MA, USA), as described (Scroyen et al 2012). Data are normalized to b-actin as internal control and expressed as the ratio P-Akt/Akt.…”
Section: Methodsmentioning
confidence: 99%
“…TaqMan gene expression assays (Life Technologies) were used to analyze the mRNA levels in SC and GON adipose tissues of adiponectin (Mm 00456425_m1) and Glut4 (Slc2a4; Mm 00436615_m1), with b-actin (Mm 01205647_g1) as housekeeping gene, as described elsewhere (Scroyen et al 2012). For peroxisome proliferator-activated receptor g (PPARg), the following primer and probe set was used: fw, ctgtcggttcagaagtgcct; rev, atctccgccaacagcttctc; probe: cccaaacctgatggcattg tgagaca.…”
Section: Methodsmentioning
confidence: 99%